2017
DOI: 10.1177/2050640616675040
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of 24‐hour ambulatory intraesophageal pH‐impedance in patients with laryngopharyngeal reflux symptoms comparable with typical symptoms

Abstract: Patients with pathologic laryngopharyngeal reflux symptom scores had lower proximal baseline impedance levels and lower proximal-to-distal ratios, which may reflect the proximal mucosal noxious effect of the refluxate. These results may indicate that laryngopharyngeal reflux symptoms may be due to chronic acid exposure in the proximal segments of the esophagus, and the proximal-to-distal ratio may be used as a new metric for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
2
19
3
Order By: Relevance
“…Previous studies reported that patients with pathologic LPR symptom scores had lower proximal BI levels and lower proximal-to-distal ratios. 15 However, in the current study, the BI levels of the proximal z3 area in the LPR group were lower and had higher proximal-to-distal ratios than the control group ratios, but the results were not statistically significant ( P > .05). In addition, the BI values of proximal z3 areas and proximal-to-distal ratios were very similar between the control and SNR groups (BI at proximal z3, 2563.5 ± 780 vs 2570.4 ± 781; proximal-to-distal ratio, 1.07 vs 1.07, respectively).…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies reported that patients with pathologic LPR symptom scores had lower proximal BI levels and lower proximal-to-distal ratios. 15 However, in the current study, the BI levels of the proximal z3 area in the LPR group were lower and had higher proximal-to-distal ratios than the control group ratios, but the results were not statistically significant ( P > .05). In addition, the BI values of proximal z3 areas and proximal-to-distal ratios were very similar between the control and SNR groups (BI at proximal z3, 2563.5 ± 780 vs 2570.4 ± 781; proximal-to-distal ratio, 1.07 vs 1.07, respectively).…”
Section: Discussioncontrasting
confidence: 77%
“…2 Studies have found lower impedance values in patients with gastroesophageal reflux disease (GERD) compared with healthy control subjects. 3 In our recent study, 4 we found that compared with GERD patients without extraesophageal symptoms, patients with extraesophageal symptoms (related to GERD) had similar distal esophageal impedance but significantly lower proximal esophageal impedance. This may be caused by exposure of the proximal esophagus to the refluxate.…”
mentioning
confidence: 76%
“…A former study published by Sakin retrospectively included suspected LPR patients and nonerosive reflux disease patients. Proximal baseline impedance and proximal‐to‐distal ratios were found to be lower among patients with pathologic laryngopharyngeal Reflux Finding Score . However, patients with suspected esophageal motility disorders and esophagitis were all excluded and therapy outcome was not discussed in the study.…”
Section: Discussionmentioning
confidence: 99%